Draft Genome Assembly of Rhodobacter sphaeroides 2.4.1 Substrain H2 from Nanopore Data - Leidenfrost, Robert Maximilian (Microbiol Resour Announc, 2020)
Rhodobacter sphaeroides is a purple bacterium with complex genomic architecture. Here, a draft genome is reported for R. sphaeroides strain 2.4.1 substrain H2, which was generated exclusively from Nanopore sequencing data.